Computational insight on the structural, mechanical and thermal properties of Cu₂CdSnSe₄ and Cu₂HgSnSe₄ adamantine materials - Bensalem, S.; Chegaar, M.; Bouhemadou, A. (Condensed Matter Physics, 2016)
Through first-principles calculation based on the density functional theory (DFT) within the pseudo potentialplane wave (PP-PW) approach, we studied the structural, mechanical and thermal properties of Cu₂CdSnSe₄ and Cu₂HgSnSe₄ adamantine materials. The calculated lattice parameters are in good agreement with experimental and theoretical reported data. The elastic constants are calculated for both compounds using the static finite strain scheme. The hydrostatic pressure action on the elastic constants predicts that both materials are mechanically stable up to 10 GPa. The polycrystalline mechanical parameters, i.e., the anisotropy factor (A), bulk modulus (B), shear modulus (G), Young’s modulus (E), Lame’s coefficient (λ) and Poisson’s ratio (ν) have been estimated from the calculated single crystal elastic constants. The analysis of B/G ratio shows that the two studied compounds behave as ductile. Based on the calculated mechanical parameters, the Debye temperature and the thermal conductivity have been probed. In the framework of the quasi-harmonic approximation, the temperature dependence of the lattice heat capacity of both crystals has been investigated.